2007
DOI: 10.1021/jp073713d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Heterogeneous Nucleation and Growth of Argon at Polyethylene Films

Abstract: Heterogeneous nucleation and growth of supersaturated argon vapor at polyethylene surfaces is investigated using molecular dynamics simulation. The specific system is chosen as model for high wettable systems. The simulations are conducted in a nonequilibrium ensemble which includes heat transfer during the condensation process. Temporary density and temperature gradients are developed in the vapor phase. The gradual transition from nearly adsorption behavior close to the binodal to heterogeneous nucleation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Along with the BK-THNY melting scenario, several possible melting mechanisms were suggested. Phase transitions between fluids and solids can occur in 2D and quasi-2D systems, for instance, during heterogeneous crystallization 35,36 , condensation on the surface and subsequent crystallization in the plane 37 , formation of clusters of particles on the fluid surface 38,39 , and in systems of attracting like-charged particles 40,41 .…”
Section: Introduction II Introductionmentioning
confidence: 99%
“…Along with the BK-THNY melting scenario, several possible melting mechanisms were suggested. Phase transitions between fluids and solids can occur in 2D and quasi-2D systems, for instance, during heterogeneous crystallization 35,36 , condensation on the surface and subsequent crystallization in the plane 37 , formation of clusters of particles on the fluid surface 38,39 , and in systems of attracting like-charged particles 40,41 .…”
Section: Introduction II Introductionmentioning
confidence: 99%
“…If two atoms are separated by a distance less than a critical value, they are regarded as being within a cluster. In this work, the critical distance is taken to be 1.5σ Ar–Ar . , Moreover, if the distance between the solid surface and any atoms in a cluster is less than 3.5σ Ar–Ar , the cluster is identified as a surface cluster. The simulation results within 12 ns, sufficient to show the evolutions, are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…For the formation of initial 2D wetting layer on the substrate, it is because of complete wetting due to the lower surface energy of the epitaxial wetting layer as compared to that of substrates. Rozas et al 27 observed a continuous transition from the layer-by-layer growth to the islands-on-layers one by increasing the supersaturation along an isotherm during the growth of supersaturated argon vapor at polyethylene surfaces. Similarly, during semiconductor heterogeneous growth, the experimental conditions can also influence the density and size of quantum dots.…”
Section: Resultsmentioning
confidence: 99%